To Free the Spirit? Motivation and Engagement of Indigenous Students - Munns, Geoff; Martin, Andrew; Craven, Rhonda (The Australian Journal of Indigenous Education, 2008)
Abstract This article directly responds to issues impacting on the social and academic outcomes of Indigenous students that were identified in the recent review of Aboriginal Education conducted by the New South Wales Department of Education and Training (NSW DET) in partnership with New South Wales Aboriginal Education Consultative Group (NSW AECG). Not surprisingly, a common theme emerging from the review was the importance of student motivation and engagement for Indigenous students of all ages. The article reports on current research into the motivation, engagement and classroom pedagogies for a sample of senior primary Indigenous students. What is of particular interest is the cultural interplay of the lived experiences of these Indigenous students with schools, teachers and classroom pedagogies. Important questions arise from an analysis of this interplay about what might “free the spirit” for these and other Indigenous students.